2017
DOI: 10.3389/fspas.2017.00051
|View full text |Cite
|
Sign up to set email alerts
|

The Overdense Environments of WISE-Selected, Ultra-Luminous, High-Redshift AGN in the Submillimeter

Abstract: The environments around WISE-selected hot dust obscured galaxies (Hot DOGs) and WISE/radio-selected active galactic nuclei (AGNs) at average redshifts of z = 2.7 and z = 1.7, respectively, were found to have overdensities of companion Submillimeter-selected sources. The overdensities were of ∼2-3 and ∼5-6 , respectively, compared with blank field submm surveys. The space densities in both samples were found to be overdense compared to normal star-forming galaxies and Submillimeter galaxies (SMGs). All of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Studies have increasingly shown that Hot DOGs reside in overdense environments, characterized by a high frequency of galactic mergers (Jones et al 2014;Jones 2017;Assef et al 2015;Díaz-Santos et al 2018;Penney et al 2019;Luo et al 2022;Ginolfi et al 2022;Zewdie et al 2023). Despite hosting powerful AGNs, the host galaxies of high-z Hot DOGs are gasrich (Penney et al 2020;Díaz-Santos et al 2021;L.…”
Section: Optical Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have increasingly shown that Hot DOGs reside in overdense environments, characterized by a high frequency of galactic mergers (Jones et al 2014;Jones 2017;Assef et al 2015;Díaz-Santos et al 2018;Penney et al 2019;Luo et al 2022;Ginolfi et al 2022;Zewdie et al 2023). Despite hosting powerful AGNs, the host galaxies of high-z Hot DOGs are gasrich (Penney et al 2020;Díaz-Santos et al 2021;L.…”
Section: Optical Emissionmentioning
confidence: 99%
“…By imaging the [C II] emission in extremely luminous DOGs (L bol > 10 14 e ) ALMA, however, Díaz-Santos et al (2021) proposed instead that this short-lived phase may be triggered by a minor merger and might occur recurrently throughout the history of the galaxy. This is particularly plausible if Hot DOGs become the brightest galaxies in clusters once the overdensities they live in (Jones et al 2014;Jones 2017;Assef et al 2015;Luo et al 2022;Ginolfi et al 2022;Zewdie et al 2023) become virialized.…”
Section: Optical Emissionmentioning
confidence: 99%